2012
DOI: 10.1097/fbp.0b013e328357bd62
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen reduces binge eating in a double-blind, placebo-controlled, crossover study

Abstract: Baclofen has shown promise in treating substance use disorders and also reduced binge frequency in an open-label trial. This placebo-controlled, double-blind, crossover study further assessed the effects of baclofen on binge eating. Twelve individuals who self-reported binge eating completed the study. Data were collected during a run-in period (no drug or placebo), placebo phase (48 days), and baclofen phase (titrated up to 60 mg daily or the maximum tolerated dose, 48 days). All the participants were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 40 publications
(69 reference statements)
0
23
0
1
Order By: Relevance
“…In light of the similarities between binge intake of highly palatable foods and drug addiction, our laboratory and others have been interested in studying the effects of medications that have been used to treat substance use disorders on overeating. For example, the GABA-B agonist, baclofen, which has been found to be effective in treating several aspects of alcohol dependence in many (Addolorato et al, 2000, 2007, 2011) but not all studies (Garbutt et al, 2010), has also been shown to aid in the reduction of binge eating behavior in both preclinical and clinical studies (Buda-Levin et al, 2005; Broft et al, 2007; Berner et al, 2009; Corwin et al, 2012). Additionally, baclofen has shown some success in inhibiting weight gain in animals and promoting weight loss in clinical samples (Sato et al, 2007; Arima and Oiso, 2010; Patel and Ebenezer, 2010).…”
mentioning
confidence: 99%
“…In light of the similarities between binge intake of highly palatable foods and drug addiction, our laboratory and others have been interested in studying the effects of medications that have been used to treat substance use disorders on overeating. For example, the GABA-B agonist, baclofen, which has been found to be effective in treating several aspects of alcohol dependence in many (Addolorato et al, 2000, 2007, 2011) but not all studies (Garbutt et al, 2010), has also been shown to aid in the reduction of binge eating behavior in both preclinical and clinical studies (Buda-Levin et al, 2005; Broft et al, 2007; Berner et al, 2009; Corwin et al, 2012). Additionally, baclofen has shown some success in inhibiting weight gain in animals and promoting weight loss in clinical samples (Sato et al, 2007; Arima and Oiso, 2010; Patel and Ebenezer, 2010).…”
mentioning
confidence: 99%
“…Psychotropic drugs such as topiramate, which modulate GABAergic and glutamatergic neurotransmission, have been shown to be effective in the treatment BED symptomatology, including impulsivity and lack of control with regards to over eating [49]. Moreover, baclofen, which has specific effect on GABAergic transmission, is effective in reducing binge frequency relative to placebo in individuals exhibiting binge eating symptoms [50].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, one goal of experiment 1 was to determine whether or not lard would function as an optional fat source in this binge protocol by including both daily and intermittent groups. In addition, baclofen has previously been reported to reduce binge-type consumption of shortening in this model (Buda-Levin et al, 2005;Berner et al, 2009;Corwin and Wojnicki, 2009) and to reduce binge frequency in human clinical trials (Broft et al, 2007;Corwin et al, 2012). As lard, like shortening, is used in the preparation and production of food consumed by humans, another goal of experiment 1 was to assess the ability of baclofen to reduce consumption of lard under 'binge-type' and non-'binge-type' conditions.…”
Section: General Proceduresmentioning
confidence: 98%
“…Baclofen is a GABA-B agonist that has been shown to reduce binge frequency in human clinical trials (Broft et al, 2007;Corwin et al, 2012) as well as binge size in animal studies. Although initial clinical and preclinical trials showed promising results, they reported variability in the effectiveness of baclofen.…”
Section: Introductionmentioning
confidence: 99%